Learning "goal programmning" using an interactive multimedia courseware : design factors and students' preferences - Aris, Baharuddin; Ahmad, Maizah Hura; Kok, Boon Shiong; Ali, Mohamad Bilal; Harun, Jamalludin; Tasir, Zaidatun (2006)
This paper attempts to describe a research project related to the learning of â€œGoal Programmingâ€? of Form Six students, using an interactive multimedia (IMM) courseware. The purpose of the study was to determine the suitability of the design in the multimedia courseware for the learning and studentsâ€™ preferences toward the use of the courseware compared to traditional methods of learning the topic. The treatment instrument, that is the IMM courseware, was developed by a team of experts at the Department of Educational Multimedia, Faculty of Education (multimedia courseware design and development) and the Department of Mathematics, Faculty of Science (content expert) at Universiti Teknologi Malaysia (UTM). The research instrument was in the form of a questionnaire that consisted of six main parts. Out of 114 of Year One science students, 16 students participated in the pilot study while another 40 students volunteered to participate in the actual study. Results from the analysis showed that many students agreed that this IMM courseware is user-friendly and able to support the learning of â€œGoal Programmingâ€?. Many students also prefer learning it using an IMM courseware compared to traditional methods of learning while teachers play the role of a facilitator.